2017
DOI: 10.1055/s-0043-115395
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Partial HPV Genotyping After Conization of Cervical Dysplasias

Abstract: Introduction In this retrospective study partial genotyping of human papilloma viruses (HPV) using the Abbott RealTime HighRisk HPV Test (RealTime) was compared with simple HPV detection (Qiagen Hybrid Capture 2 Test; hc2) for recurrence prediction at the first follow-up examination after conization of cervical intraepithelial neoplasia (CIN). Methods 144 women who had undergone conization for CIN between January 2007 and December 2013 were included. HPV status was determined preoperatively and at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…During the past 15 years, however, the incidence of cervical cancer has been stagnating at a low Diagnostics 2022, 12, 1748 2 of 13 level, despite advances in diagnosis and therapy [1][2][3]. Invasive cervical cancer is caused by a persistent infection with human papillomavirus (HPV) [4][5][6]. HPV is a biological carcinogen, and high-risk HPV (hrHPV) types are detected in up to 99.7% of cervical cancers [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…During the past 15 years, however, the incidence of cervical cancer has been stagnating at a low Diagnostics 2022, 12, 1748 2 of 13 level, despite advances in diagnosis and therapy [1][2][3]. Invasive cervical cancer is caused by a persistent infection with human papillomavirus (HPV) [4][5][6]. HPV is a biological carcinogen, and high-risk HPV (hrHPV) types are detected in up to 99.7% of cervical cancers [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [25] reported that HPV 16/18 was detected in a group that underwent hysterectomy after a loop electrosurgical excision procedure. Moreover, testing for postoperative HR-HPV genotypes can predict recurrence and additional surgery [19,26]. The present study showed that the HR of additional surgery was characterized by not only the surgical margin status and positive preoperative HR-HPV but also the same persistent HR-HPV genotype around conization, especially HPV 16/18.…”
Section: Discussionmentioning
confidence: 55%
“…We identified 7 eligible studies [ 8 , 9 , 17 , 19 , 20 , 23 , 32 ] including 1790 CIN patients after surgery to investigate the relationship between HPV types and persistent HPV infection and nonpersistent HPV infection. Our results revealed that there was a positive effect on persistent HPV infection between HPV 16 and other types of HPV.…”
Section: Resultsmentioning
confidence: 99%